Shadow's deadline - Stone, Mary 1968-; Rhodes, Lori (United States Mary Stone, 2022)
When death has a deadline... The late Sheriff Alden Wallace has barely been laid to rest when another body is found on Shadow Island. Once again, former FBI agent turned interim sheriff Rebecca West's vacation plans will have to wait. This time, the victim is the son of one of Shadow Island's privileged elite. Found gruesomely posed at a picnic table in the park--suffocated, choked, and shot, with a cryptic note shoved in his pants--his death is as personal as it is disturbing. And he's the first one on the killer's list. When a second young man is murdered in a similar fashion, the questions and the stakes increase. Who had so much rage against these men? A girl they treated poorly? Or were the murders somehow connected to the secretive and exclusive organization of rich men no one on the island wants to talk about? The deeper Rebecca digs, the more certain she is the Yacht Club is involved in the spate of crimes on the island...and the late Sheriff Wallace may have been covering for them. The club members will stop at nothing to keep their secrets. But Rebecca is determined to expose them, regardless of the cost. From the provocative beginning to the edge-of-your-seat conclusion, Shadow's Deadline--the third book in the Shadow Island Series by Mary Stone and Lori Rhodes--will remind you to choose your friends wisely.
111377
Keywords: Women detectives -- Fiction; Sheriffs -- Fiction; Murder -- Investigation -- Fiction; Yacht clubs -- Fictio; Secrecy -- Fiction; Detective and mystery fiction; Fiction